2021
DOI: 10.3389/fnins.2021.731109
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Motor Outcome of Subthalamic Nucleus Deep Brain Stimulation for Parkinson’s Disease Using Quantitative Susceptibility Mapping and Radiomics: A Pilot Study

Abstract: BackgroundEmerging evidence indicates that iron distribution is heterogeneous within the substantia nigra (SN) and it may reflect patient-specific trait of Parkinson’s Disease (PD). We assume it could account for variability in motor outcome of subthalamic nucleus deep brain stimulation (STN-DBS) in PD.ObjectiveTo investigate whether SN susceptibility features derived from radiomics with machine learning (RA-ML) can predict motor outcome of STN-DBS in PD.MethodsThirty-three PD patients underwent bilateral STN-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…SN radiomic features have been employed in ML algorithms to discriminate between patients with PD and healthy subjects ( Li et al, 2019 ; Xiao et al, 2019 ; Xiao et al, 2021 ). The recent pilot study ( Liu et al, 2021 ) demonstrated that SN radiomic features combined with the binary logistic regression analyses could predict motor outcome of STN-DBS in PD with 82% accuracy (AUC = 0.85).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SN radiomic features have been employed in ML algorithms to discriminate between patients with PD and healthy subjects ( Li et al, 2019 ; Xiao et al, 2019 ; Xiao et al, 2021 ). The recent pilot study ( Liu et al, 2021 ) demonstrated that SN radiomic features combined with the binary logistic regression analyses could predict motor outcome of STN-DBS in PD with 82% accuracy (AUC = 0.85).…”
Section: Discussionmentioning
confidence: 99%
“…The recent growth of radiomics studies for different neurodegenerative brain disorders was also directed to PD and mostly to cortical and subcortical structures ( Wu et al, 2019 ). Recently, it was also found that substantia nigra susceptibility features from radiomics could predict global motor and rigidity outcomes of STN-DBS in PD and suggested a predictive machine learning model for STN-DBS patient selection ( Liu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative susceptibility mapping (QSM) provides a direct measure of iron deposition by using a deconvolution method and it has been demonstrated as the most sensitive quantitative MRI technique for detecting significant increases in iron in PD subjects 16 . A previous study established a machine‐learning model on QSM radiomics in the SN and attempted to predict the effect of DBS using this model 17 . However, most studies report only mean value of the region of interest (ROI), and the relationship between the iron spatial distribution in deep gray matter nuclei and motor outcome is unclear.…”
mentioning
confidence: 99%
“…16 A previous study established a machine-learning model on QSM radiomics in the SN and attempted to predict the effect of DBS using this model. 17 However, most studies report only mean value of the region of interest (ROI), and the relationship between the iron spatial distribution in deep gray matter nuclei and motor outcome is unclear.…”
mentioning
confidence: 99%